Application of Multi Objective Optimization Method Based on Ratio Analysis (MOORA) in the Election of RT Kavling Risma Jihan Akbar Chairperson - Hartati, Tri; Hikmah, Noer; Yani, Desri (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The RT chairman is a task and responsibility given to someone in a residential environment. The election of the RT chairman is something that needs attention because it concerns the welfare of residents in the environment. If the elected RT chairman does not carry out his duties and obligations properly, it can be a loss that must be borne together by the residents. Therefore, candidates who run for office must have the criteria to be able to lead the village/area where they live. In the election process, there are sometimes differences of opinion between residents which often cause disputes. To avoid this, in the process of electing the RT chairman for the 2025-2030 period in the Risma Jihan Akbar plot which will take place, a study was conducted on the assessment of criteria using the MOORA method. This method is very effective and efficient for assessing and ranking candidates who run for office. The purpose of the study is to assist the committee in making decisions on determining the RT chairman in the Risma Jihan Akbar plot environment. The final result of this study is the ranking of candidates who meet the criteria requirements. The first rank with a total score of 0.53 was obtained by candidate c5, then the second rank was candidate c4 with a total score of 0.45 and the third rank with a score of 0.45 was obtained by candidate c2.